The Influence of the Work Environment and Promotion on Job Satisfaction of BPN West Aceh Employees - Riana Wandira (International Journal of Social Service and Research, 2023)
This survey was conducted at the West Aceh BPN Office located in Jl. Swadaya, Meulaboh, and West Aceh. With the aim of discouraging the consequences of environmental conditions and promotions for the enjoyment of the work of BPN Aceh West personnel. In the population survey all personnel of the BPN Aceh west totaling 37 people. Determination of the sample using the saturated sampling method with all the population being sampled so the number of samples in this survey is 37 people. In this survey, the researcher applies an associative quantitative design. Materials are obtained by distributing questionnaires in the form of questions to be answered by the respondent. Assessment of data using multiple linear regression analysis. Source of data comes from primary data, Data obtained directly from respondents. The results of this survey prove that the environment and promotion either partially or simultaneously have a positive and significant impact on employee satisfaction at the west BPN Aceh office. With the results of the determinant coefficient being able to explain the environment and promotion of employee satisfaction as much as 64.5% the remaining 35.5% was obtained from other factors and was not examined in this survey model.